SEASONAL BIOLOGICAL WATER QUALITY ASSESSMENT OF RIVER KSHIPRA USING BENTHIC MACRO-INVERTEBRATES - Archna, Akhand; Sharad, Shrivastava; Pratibha, Akhand (International Journal of Research -GRANTHAALAYAH, 2015)
The water quality of River Kshipra in stretch of 195 km was studied for water quality status using benthic macro invertebrates for all three seasons’ monsoon, winter and summer. The River water quality is subject to severe domestic and industrial pollution at compete stretch of River. In the present investigation a total of 13 Orders of macrobenthic fauna i.e. Ephemeroptera, Trichoptera, Placoptera, Coleoptera, Hemiptera, Odonata, Crustacea, Diptera, Pulmonata, Operculata, Pulmonata, Oligochaeta and Hirudinea belong to 3 Phylum’s Arthropoda, Mollusca and Annelida were reported. Arthropoda was the most dominant group in all seasons. On seasonal comparison of benthic fauna is observe that abundance were decreasing order were, Winter > Monsoon > summer. To monitor the water quality samples from two years (2010-12) from different stations were collected monthly. The works highlighted the condition of the River water in various seasons with respect of the seasonal abundance of the benthic macro-invertebrates organisms mentioned above.